2013
DOI: 10.1186/1477-7525-11-124
|View full text |Cite
|
Sign up to set email alerts
|

‘It is not going to change his life but it has picked him up’: a qualitative study of perspectives on long term oxygen therapy for people with chronic obstructive pulmonary disease

Abstract: BackgroundLong-term oxygen therapy (LTOT) extends life in patients with chronic obstructive pulmonary disease with severe hypoxaemia. Questionnaire-based studies of the effects of LTOT have not suggested uniformly positive findings. The few qualitative studies suggest that patients report benefits but also concerns about dependency on oxygen therapy. The aim of the study was to explore the views and experiences of COPD patients, their carers and the healthcare professionals who deliver these services, on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Yet our study has shown that, to a large extent, caregivers consider oxygen to have a significant role in the relief of refractory breathlessness. These findings are supported by those by Goldbart et al who found that caregivers equated LTOT as important for patients' quality of life [17]. Our findings go much further however, highlighting how LTOT, to a large extent was regarded by caregivers as critical in keeping the person they are caring for alive.…”
Section: Discussionsupporting
confidence: 80%
“…Yet our study has shown that, to a large extent, caregivers consider oxygen to have a significant role in the relief of refractory breathlessness. These findings are supported by those by Goldbart et al who found that caregivers equated LTOT as important for patients' quality of life [17]. Our findings go much further however, highlighting how LTOT, to a large extent was regarded by caregivers as critical in keeping the person they are caring for alive.…”
Section: Discussionsupporting
confidence: 80%
“…Randomisation of 122 LTOT patients to follow-up with a hospital-based homecare programme (monthly phone call, home visits every 3 months, and home or hospital visits on a demand basis) or conventional medical care, demonstrated significantly decreased costs in the homecare follow-up group, which was mainly due to a reduction in use of hospital resources, despite the cost of running the service itself 59. Reports from focus groups60 and case series53 highlight the importance of education from specialist nurses or physiotherapists in increasing compliance and addressing patient concerns.…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…Similar studies were conducted on ICs of patients with COPD [7, 8], but to our knowledge, this is the first study to focus on the impact of O 2 on ICs of PF patients.…”
Section: Discussionmentioning
confidence: 80%